Knowledge and Awareness on Swine Origin Influenza A(H1N1) Among Health Care Providers and Civil Employees in a Tertiary Level Hospital, Dhaka Bangladesh - A Rahim, Md; Chowdhury, Mohammad Mainul Hasan; Selimuzzaman, S M (Bangladesh Armed Forces Medical Journal, 2024)
Background: Swine Origin Influenza A(H1N1) viruses create yearly epidemics and rarely pandemics that cost millions of lives worldwide. Health care providers and civil employees at hospital can help in prevention of transmission of influenza by acquiring knowledge and awareness. Methods: A descriptive cross-sectional study was conducted at Combined Military Hospital Dhaka from July to December 2023. Total 213 participants were interviewed that comprises doctors, nurses, medical assistants and civil employees. Purposive sampling technique was used to collect data. Face to face interview was done through a pre-tested semi-structured questionnaire. Data were analysed by using Statistical Package for the Social Sciences (SPSS) version 25.0. Informed consent were obtained from the respondents addressing proper ethical issues. Results: In this study out of total participants 70.4% had previously heard about H1N1 influenza A. Total 38% participants said that internet was found as major source of information. Among the participants 64.3% told fever was common symptom and use of facemask at duty hour was consented by 33.8% as an important means for prevention. Maximum (66.3%) civil employees do not know about washing hand after contact as a preventive procedure leading to spread of infection. Maintaining distance as preventive measures observed by 13.6% participants. Moreover, all participants were aware of transmission through droplet infection except civil employees. In the present study, 50% doctors and 38.1% nurses had knowledge that drug Oseltamivir is very effective against swine Influenza A(H1N1). Remarkable differences were identified among doctors, nurses, medical assistants and civil employees regarding knowledge of quarantine and availability of vaccine. RT-PCR laboratory test is the confirmatory method to defect swine influenza A(H1N1) were exactly known by 9.9% participants, while 70.9% participants don't know the confirm diagnostic method. Conclusion: Knowledge and awareness regarding swine influenza A(H1N1) was low among study participants. For controlling epidemic or even pandemic, awareness by mass media is important. Remarkable gap observed regarding knowledge and awareness about swine influenza A(H1N1) among the health care providers and civil employees, needs to be addressed by proper training and motivation. Bangladesh Armed Forces Med J Vol 57 No (1) June 2024, pp 1-7